Nigeria : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Alternate Executive Director for Nigeria. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
The Nigerian economy is at a critical juncture. A weak pre-crisis economy characterized by falling per capita income, double-digit inflation, significant governance vulnerabilities and limited buffers, is grappling with multiple shocks from the COVID-19 pandemic. Real output is projected to contract by 3.2 percent in 2020, with a weak recovery likely to keep per capita income stagnant and no higher than the 2010 level in the medium term. Policy adjustment and reforms are urgently needed to navigate this crisis and change the long-running lackluster course.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Nigeria